The effect of diffuse reflections on spatial discrimination in a simulated concert hall - Robinson, Philip; Pätynen, Jukka; Lokki, Tapio (The Journal of the Acoustical Society of America, 2013)
This letter presents results from a study on diffusive architectural surfaces and auditory perception. Spatial discrimination of multiple sources is investigated in a simulated performance venue with various diffusive surface treatments. Simulations were generated with closely spaced sound sources on the stage of a concert hall and a listener in the audience area. Subjects were asked to distinguish signals in which pairs of simultaneous talkers were presented at various lateral separations, in halls with flat or diffusive surfaces. The experiments reveal that discriminating differences in the lateral arrangement of sources is possible at narrower separation angles when reflections come from flat rather than diffusive surfaces.